Structure, DFT studies and evaluation of catechol oxidase (CO) mimic activity of mononuclear Co(II) complexes derived from aminoalcohols: an experimental and theoretical approach. Issue 19 (15th November 2022) - I., Mantasha; Zeeshan, Mohd; Yadav, Oval; Ansari, Azaj; Qasem, Khalil M. A.; Akhtar, Muhammad Nadeem; AlDamen, Murad A.; Shahid, M.
Abstract: The impetus to modeling of enzyme mimics comes from their potential to provide insight to the alternate mechanistic pathways of the native enzymes. The present study demonstrates the syntheses and characterization of two different cobalt(II) complexes, [Co(pdm)(Phen)Cl]Cl·H2 O (1 ) and [Co(pmmH)2 (SCN)2 ] (2 ) with the aminoalcohol ligands such as pyridine-2, 6-dimethanol (pdmH2 ) or 2-pyridinemonomethanol (pmmH) and their assessment as catechol oxidase (CO) enzyme mimic. Single Crystal X-ray diffraction and powder X-ray diffraction data suggest the octahedral environment around the Co(II) ion and the complexes form extensive 1D or 2D propagating network as a result of non-covalent interactions (O···H and C-H···π). TD-DFT calculations were used to explain the spectral bands obtained during the UV-Vis absorption studies and it is ascertained that the transitions were mainly of the intra-ligand charge transfer (ILCT) type. The catecholase biomimetic catalytic activity of the synthesized complexes has been investigated in detail and the kinetics is also performed. The results obtained show that both the complexes catalyze the aerobic oxidation of catechol to the corresponding o-quinone. The K cat value for 1 is 106.99 h ‒1 and for 2 is 90.32 h ‒1 in methanol. It may be mentioned here that 1 and 2 are effective catalysts, with the order of activity being 1 > 2 . The order of enzymatic activity is well justified by CV and DFT studies. Communicated by Ramaswamy H. Sarma